Depósitos conglomeráticos da paleo-planície do Rio Tietê: evento de agradação fluvial na evolução da Depressão Periférica Paulista - Breda, Caio [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The conglomeratic Cenozoic deposits located in the sourroundings of the Laras district, in the city of Laranjal Paulista, SP, constitute packages of decametric thickness that consists of wide flat-topped hills (490 to 570 meters of altitude) developed on stratigraphic units of the Paraná Basin. The conglomerates lie in unconformable on the Teresina Formation (Permian) and, secondarily, on the Piramboia Formation (Permo-Triassic). The studied conglomeratic deposits are firstly described here and show mappable occurrence of the scale of 1: 25.000, so that they can constitute an independent lithostratigraphic unit. The deposits are essentially composed of poorly selected sandy matrix polymorphic orthoglomerates, sometimes ferricretized due to recent diagenetic processes. The conglomerates locally occur intercalated with pebbly sandstones with grooved cross stratification, forming channels with ten meters of lateral extension and many meters of thickness. The analysis of clasts provenance was carried out in four stations measuring in the entire length of the deposits, with the characterization of the lithologies and measurement of the major, minor and intermediate axes of 1,218 clasts. The results of gravel petrography show a higher frequency of lithotypes resistant to transport in the southeast portion of the area of occurrence of the deposits. Predominate clasts of silexites, quartzites and vein quartz, well rounded and oblate, suggesting transport over a long distance from the source area in the crystalline basement. In the northwestern portion, occurs less resistant litothypes and subangled clasts, represented by oolitic carbonates and coquinas, both silicified, predominate. These lithotypes suggest erosion of the Teresina Formation and short transport from the source area in Paleozoic terrains existing in the Paulista Peripheral Depression. Paleocurrent measurements measured in cross stratification and pebble imbrication indicate paleoflux...

Os depósitos cenozoicos conglomeráticos situados nos arredores do distrito de Laras, município de Laranjal Paulista, SP, constituem pacotes de espessura decamétrica que compõe colinas amplas de topo aplainado (490 a 570 metros de altitude) desenvolvidas sobre unidades estratigráficas da Bacia do Paraná. Os conglomerados jazem em discordância sobre a Formação Teresina (Permiano) e, secundariamente, sobre a Formação Pirambóia (Permo-Triássico). Os depósitos conglomeráticos estudados constituem ocorrência inédita e mapeável na escala de 1:25.000, de modo que podem constituir uma unidade litoestratigráfica independente. Os depósitos são constituídos essencialmente por fácies de ortoconglomerados polimíticos com matriz arenosa, mal selecionados, por vezes ferricretizada devido a processos diagenéticos recentes. Os conglomerados localmente ocorrem intercalados com arenitos conglomeráticos com estratificação cruzada acanalada, formando canais com dezenas de metros de extensão lateral e vários metros de espessura. A análise de proveniência de clastos foi realizada em quatro estações de medidas em toda a extensão dos depósitos, com a caracterização das litologias e medição dos eixos maiores, menores e intermediários de 1.218 clastos. O resultado das medições dos clastos evidenciou maior frequência de litotipos resistentes ao transporte na porção sudeste da área de ocorrência dos depósitos. Predominam clastos de silexitos, quartzitos e quartzo de veio, bem arredondados e de formato oblato, sugerindo transporte por longa distância a partir de área fonte no embasamento cristalino. Na porção noroeste predominam depósitos de clastos menos resistentes e subangulosos, representados por carbonatos oolíticos e coquinas, ambos silicificados. Estes litotipos sugerem erosão da Formação Teresina e transporte curto a partir de área fonte em terrenos paleozoicos existentes na Depressão Periférica...
Keywords: Sedimentação e depósitos; Geologia estratigráfica; Petrologia; Geologia estratigráfica - Cenozóico; Fácies (Geologia); Tietê, Rio (SP); São Paulo (Estado)